In Times Past: Exploring an Artifact From the Archives of The New York Times. - DUNLAP, DAVID W. (New York Times, 2024)
The article looks at the strikes staged against the U.S. newspaper "The New York Times" by different labor unions, including the Times Tech Guild which began on November 4, 2024, the New York Times Guild in December 2022, and the Local 6 of the International Typographical Union in 1962.